Ethical Leadership and Whistleblowing: Mediating Role of Stress and Moderating Effect of Interactional Justice - Muhammad Osaid Rabie; Marlin Abdul Malek (SEISENSE (PRIVATE) LIMITED, 2020)
Purpose- Prevalence of corporate frauds is critical, therefore, identifying and institutionalizing the bad apples in the barrel which are engaged in wrongdoings is much needed and must be brought to the lights through whistleblowing. Design/Methodology- Data were collected from the South Asian countries through a structured questionnaire from the employees of the telecom sector. Three hundred twenty-nine samples were gathered to test hypothesized relationships. Findings- Results showed that whistleblowing intentions of employees through psychological stress mediates the behaviors of their leaders, which turns ethical leadership at the workplace. Further, ethical leadership positively impacts employees’ intention to blow the whistle at the workplace. Furthermore, the analysis showed that interactional justice moderates the relationship between ethical leadership and intention to blow the whistle of employees Practical Implications- This research gives a different perspective to the managers to develop such a culture that enables an honest and trustworthy environment, which may enable the employees to point out the wrongdoings they witness while working at the workplace.